Principled governance when everything matters - Fushtey, David S. (Emerald Publishing Limited : Information Age Publishing Inc., 2021)
"for Directors, Managers, Counsellors and Students, indeed for everyone challenged to answer - how do we get along It's taken the democratic world half a millennium to shift our systems of governance from the power of might to the rule of law. We have learned, from centuries of errors (and trials), to create a framework of regulation, accountability and oversight. Yet modern systems of governance, now widely practiced, are still little understood. Principled Governance when Everything Matters is a guided tour of the field, led by an expert who spent three decades at boardroom and council tables, watching and advising directors and managers in business and civil society. This accessible volume will be invaluable to new directors and managers. It's not a "how-to" book, but a volume to give context and background, to help you understand how to think about the responsibilities of governance if you hope to do it well. Principled Governance is based on David S. Fushtey's comprehensive academic text The Director and Manager: Law and Governance in a Digital Age - Machiavelli Had It Easy, reviewed and revised by a team of subject-area experts and communicators, who have drawn out the most useful, relevant - often crucial lessons. The result is an engaging guidebook for students of business, civil society and law, and for the continuing education of directors and the executives who advise them"-- Provided by publisher.
"This book is a distillation of the wisdom and meaning to be found in David S. Fushtey's masterwork: The Director and the Manager: Law and Governance in a Digital Era: Machiavelli Had It Easy" --ECIP foreword.
Keywords: Fushtey, David S. -- Director and the manager.; Corporate governance -- Law and legislation.; Business & Economics -- Corporate Governance.; Corporate governance: role and responsibilities of boards and directors.; elektronické knihy; electronic books